Some directions are about solution problems from overcharge transport nodes by type BDM - Kirianov, O. F.; Pereverzieva, H. H. (Science and Transport Progress, 2011)
The results of traffic intensity investigation on Kremenchuk regulated road crossings are presented. Optimum organizational measures for diminishing of load factor are considered. The operational modes for traffic lights ator the isolated crossing and mutually dependent junction are calculated.